PENGARUH LATIHAN BOX JUMPS DAN TUCK JUMPS TERHADAP HASIL LOMPAT JAUH SISWA KELAS X SMA NEGERI 2 PEKALONGAN TAHUN 2022 - Kunto Aribowo; Hermawan Hermawan; Moh. Nasution; Kriswantoro Kriswantoro (Universitas Negeri Semarang, 2023)
The importance of physical exercise in the long jump sport because the long jump is a sport that requires strength and quite dominant muscles in it, namely the leg muscles. Lack of learning in implementing activities to increase leg muscle strength. This study aims to determine the effect of box jumps and tuck jumps training on the results of the X grade students of SMA Negeri 2 Pekalongan. This research method is quantitative with an experimental approach and entered into the Pre Experimental design type with the category of Pre-test and Post-test Group. The instrument used is the long jump test. The research subjects were 20 students of class X SMA Negeri 2 Pekalongan. The data analysis technique used the t test. The results of the t test obtained are t arithmetic (5.515) > t table (2.845) then Ha is accepted and Ho is rejected which means it shows that box jumps affect the long jump results of class X students at SMA Negeri 2 Pekalongan, which states t count (4.638) > (2.845) then Ha is accepted and Ho is rejected, which means it shows that tuck jumps affect the long jump results of class X SMA Negeri 2 Pekalongan. The conclusion is that there is a significant effect on the long jump results of class X students of SMA Negeri 2 Pekalongan.